Tinjauan Peranan Koder Dalam Pengajuan Berkas Klaim BPJS Kesehatan Pasien Rawat Inap Di RSUD DR. R.M. Djoelham Kota Binjai - Mordekhai Immanuel Sitorus; Noor Yulia; Puteri Fannya; Nanda Aula Rumana (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Submission of claim files to BPJS Health is carried out every 10th of the month, BPJS Health will provide information whether the claim file is feasible or not. If the claim file is not feasible, it needs to be corrected. The purpose of the research is to describe the role of the coder in filing claims for BPJS Health inpatients at RSUD Dr. R.M. Djoelham Binjai City. The research method used is descriptive method with a quantitative approach. The sample uses 43 claim files returned by BPJS Health in April and May 2021 and also interviews with two coders. Data is collected by using observation with a checklist instrument and interviews with interview guidelines. The result shows that the hospital does not have standard operating procedures related to the submission of BPJS Health claim files, from 276 files (100%) submitted in April and May 2021, there were 233 files (84,42%) that deserve to be claimed and 43 files (15,58%) that were returned (not eligible). The reasons for the return were due to confirmation of diagnosis (18,60%), medical support (25,58%), indications for hospitalization (16,28%), coding (11,63%), purification failure (6,98%) and other causes (20,93%). The roles of the coder in handling claim files are assembling, determining the primary diagnosis code and secondary diagnosis based on ICD-10, determining the code of action (procedure) based on the ICD-9-CM, and coordinating with various internal parties for the completeness of the BPJS Health claim file. Suggestions for hospital to make standard operating procedures related to claim files submission and coders to be more thorough in preparing the complete claim files.